The competitiveness of EU regions - Jana Kourilova; Rene Wokoun; Milan Damborsky; Nikola Krejcova (European Regional Science Association (ERSA), 2012)
The competitiveness of EU regions This paper results from the project financed by the Grant Agency of the Czech Republic (GA ÈR). The project was carried out by the research team consisting of both The Centre of Regional and Administrative Studies and The Regional Studies Department's members in 2009 -2011. The introductory part of the paper is focused on the theoretical background with a special emphasis on the concept definition and determination of factors of the regional competitiveness. The concept of competitiveness is relatively new in the economics and the economic geography. In fact, there are no general definitions, the concept is mostly related to a specific issue. Micro-oriented definitions consider the competitiveness as a success in selling products or services on open markets. The macro-economic view is much more variable. It is often associated with an economic development of a sustainable character. The social and environmental aspect is also closely observed as well as the impact of the regional economic growth on other regions, in the sense of whether or not the economic growth is realized at the expense of other regions. The following part of the paper, based on the methodology and index defined for this purpose, assesses the competitiveness of EU regions on the NUTS II level. The regional competitiveness index was compiled on the basis of available Eurostat data. Next part of the paper presents the key factors of the regional competitiveness. Factors are classified as universal and specific. Concerning universal factors, regions with a high level of competitiveness mostly have an important economic centre; these are often metropolitan regions of member states (London, Stockholm, Paris, Prague) with a significant share of services and existence of both public and private decision-making headquarters. In non-metropolitan regions with a high level of competitiveness, there is an economic centre- city with a share of services, R&D and innovation sector. Competitive regions (or their centres) are mostly well connected with the transport infrastructure, especially TEN-T, national highways and international airports. Such regions are important air, rail, road or water transport junctions. One of the key aspects of the regional competitiveness is the concentration of scientific, R&D and innovative institutions often linked to tertiary educational institutions. In general, the educational structure with a high proportion of tertiary or higher secondary educated population (corresponding to the Czech system of secondary education with the school-leaving examination-maturita) is another aspect of a competitive region. The institutional conditions also determine the regional competitiveness and development. Specific factors of the regional competitiveness are the tourism potential, natural sources and the technical infrastructure.
Keywords: R11; 330; region; competitiveness; factors; European Union; NUTS II